2012
DOI: 10.1038/bjc.2012.237
|View full text |Cite
|
Sign up to set email alerts
|

MET in gastric carcinomas: comparison between protein expression and gene copy number and impact on clinical outcome

Abstract: Background:The aim of this study was to compare gene copy number (GCN) and protein expression of MET and to evaluate their prognostic roles in gastric carcinomas.Methods:MET protein expression and gene amplification (GA) status were determined by immunohistochemistry (IHC) and silver in-situ hybridisation (SISH), respectively, in a large series of gastric carcinoma.Results:Protein overexpression was observed in 104 of 438 cases, with IHC 2+ in 94 and IHC 3+ in 10, and high polysomy of chromosome 7 and GA were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
191
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(214 citation statements)
references
References 30 publications
20
191
2
1
Order By: Relevance
“…5,7,11,14,[16][17][18][19][20][21][22][23]33 Although MET expression showed poor prognostic effects on gastric carcinomas, 7,18,20,21,23 most studies were performed 410 years ago 5,7,17,[19][20][21][22] and interpreted either cytoplasmic or membranous positivity only 5,17-21 without considering intensity. In a recent large cohort study with gastric cancers with the same MET monoclonal antibody as ours, interpretation of membranous staining, which was used for HER2, failed to find any clinical significance and not all MET 3 þ cases exhibited amplification of MET gene.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5,7,11,14,[16][17][18][19][20][21][22][23]33 Although MET expression showed poor prognostic effects on gastric carcinomas, 7,18,20,21,23 most studies were performed 410 years ago 5,7,17,[19][20][21][22] and interpreted either cytoplasmic or membranous positivity only 5,17-21 without considering intensity. In a recent large cohort study with gastric cancers with the same MET monoclonal antibody as ours, interpretation of membranous staining, which was used for HER2, failed to find any clinical significance and not all MET 3 þ cases exhibited amplification of MET gene.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent large cohort study with gastric cancers with the same MET monoclonal antibody as ours, interpretation of membranous staining, which was used for HER2, failed to find any clinical significance and not all MET 3 þ cases exhibited amplification of MET gene. 16 The lack of a reliable method for evaluating MET immunohistochemistry has caused discrepancies in previous studies. In our comprehensive study, we first proved that both membranous and cytoplasmic MET staining correlate well with mRNA expression levels, amplification of MET gene and clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, recent IHC studies performed on gastric tumour samples have reported cMET over-expression in 4-63% of cases [72][73][74][75][76][77] and various studies performed in ovarian cancer estimate high expression of cMET to be present in 11-68 % of cases [30,22,23,26,25] (Table 1). The majority of the estimates above come from IHC studies, using a number of different antibodies, but no consensus on scoring criteria yet exists, nor whether cytoplasmic or membranous staining for cMET is important.…”
Section: Ihc For Cmetmentioning
confidence: 99%